Analisis Komposisi dan Kandungan Karotenoid Total dan Vitamin A Fraksi Cair dan Padat Minyak Sawit Kasar (CPO) Menggunakan KCKT Detektor PDA - Syahputra, M. Rio; Karwur, Ferry F; Limantara, Leenawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
This study was carried out on two phases of Crude Palm Oil (CPO) to determine the total and composition ofcarotenoid and vitamin A content. Total of carotenoid was analyzed using spectrophotometer UV-Vis, and then theresult was calculated by Gross (1991) equation. The vitamin A content was calculated by NAS-NRC equation (1974).The type and composition of both phases of CPO were determined by Choo’s method (1994) by using HPLC withPhoto Diode Array (PDA) detector. The sample was prepared in two methods, with and without saponification. Theresult shows that total carotenoids in liquid and solid phase of CPO are 536 ± 13.2 g/g (liquid), 352 ± 17.7 μg/g(solid) and the vitamin A were 89.4 ± 2.2 RE (liquid), 58.7 ± 3.0 RE (solid), respectively. The carotenoid compositionsof both phases of CPO were dominated by - and -carotenes. The result shows that - and -carotenes preparedby saponification method in liquid phase are 29.03% and 60.88%, and without saponification (direct method) are28.14% and 59.44%. The result for solid phase shows that - and -carotenes by saponification are 25.89% and60.81%, and without saponification (direct method) are 30.00% and 56.92%. The research also shows the advantagesof using HPLC with PDA detector for identification and analysis of type and carotenoid composition.